Determination of ED90s of Phenylephrine and Norepinephrine Infusion for Prevention of Spinal Anesthesia-Induced Hypotension in Patients with Preeclampsia During Cesarean Delivery - Tan H; Chen Y; Jiang Y; Sun X; Ye W; Zhu X; Xiong X (Dove Medical Press, 2024)
Haijie Tan,1,* Yi Chen,2,* Yan Jiang,1 Xiaojing Sun,1 Wei Ye,1 Xuefang Zhu,1 Xiangsheng Xiong1 1Department of Anesthesiology, The Fifth People's Hospital of Huaian, Huaian, People's Republic of China; 2Department of Anesthesiology and Perioperative Medicine, General Hospital of Ningxia Medical University, Yinchuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiangsheng Xiong, Department of Anesthesiology, The Fifth People's Hospital of Huaian, Huaian, People's Republic of China, Email 158193942@qq.comBackground: Vasopressors remain an important strategy for managing spinal anesthesia-induced hypotension in women with preeclampsia. The aim of this study was to investigate the ED90s and efficacy ratio of phenylephrine and norepinephrine in managing spinal anesthesia-induced hypotension in women with preeclampsia during cesarean delivery.Methods: 60 women with preeclampsia, who underwent cesarean delivery, were randomly assigned to receive either a continuous intravenous infusion of phenylephrine or norepinephrine following spinal anesthesia. The initial dosage of phenylephrine or norepinephrine for the first women was 0.5 or 0.05 μg/kg/min, respectively, and subsequent infusion dosages were adjusted based on their efficacy in preventing spinal anesthesia-induced hypotension (defined as a systolic blood pressure less than 80% of the baseline level). The incremental or decremental doses of phenylephrine or norepinephrine were set at 0.1 or 0.01 μg/kg/min. The primary outcomes were the ED90s and efficacy ratio of phenylephrine and norepinephrine infusions for preventing spinal anesthesia-induced hypotension prior to delivery.Results: The results obtained from isotonic regression analysis revealed that the ED90 values of the phenylephrine and norepinephrine group for preventing spinal anesthesia-induced hypotension were 0.597 (95% CI: 0.582- 0.628) and 0.054 (95% CI: 0.053- 0.056) μg/kg/min, respectively, with an efficacy ratio of 11.1:1. The results of Probit regression analysis revealed that the ED90 values were determined to be 0.665 (95% CI: 0.576- 1.226) and 0.055 (95% CI: 0.047- 0.109) μg/kg/min, respectively, with an efficacy ratio of 12.1:1.Conclusion: The administration of 0.6 μg/kg/min phenylephrine and 0.05 μg/kg/min norepinephrine has been found to effectively manage a 90% incidence of spinal anesthesia-induced hypotension in women with preeclampsia.Keywords: ED90, phenylephrine, norepinephrine, spinal anesthesia-induced hypotension, preeclampsia, cesarean delivery